Sleep Quality Profile of Mining Workers Based on Pittsburgh Sleep Quality Index (PSQI) - Leonardo Lubis; Tiara Kusumawiyanti; Gita Tiara Dewi Nasution; Febi Dwirahmadi (Media Kesehatan Masyarakat Indonesia, 2022)
The number of work accidents in Indonesia and in the world is quite high, particularly in the mining sector. One of the factors that cause occupational accidents is poor sleep quality. Therefore good quality sleep is needed to reduce the risk of accidents. This study aims to describe the sleep quality of mining workers based on age, occupational category, and Body Mass Index (BMI). The research uses a descriptive design with a cross-sectional method. Data was collected from PT Borneo Indobara in 2020, as many as 120 workers. PSQI (Pittsburgh Sleep Quality Index) is used as an instrument. Then, sleep quality was reported in age, BMI, and occupational categories. The result shows that workers at PT Borneo Indobara are dominated by the age range of 21-40 years old (80%), working as operators (70.83%), and having normal BMI (56.67%). Most of the poor sleep quality is experienced by the worker with age range 18-20 years old (90.91%), working as a leader/officer (100%), and obesity as a BMI category (88.89%). Most of PT. Borneo Indobara employees have poor sleep quality based on the PSQI score, so that the management of PT. Borneo Indobara can use this research as employee evaluation data and can prepare treatment for the employees.